How Direct Citizen Participation Affects the Local Government Financial Condition: A Case of Participatory Budgeting in South Korea - Park, HyungGun; Yoon, Sungil; Shine, B. (Javnost-The Public, 2023)
In theory, direct citizen engagement in budgeting helps local governments reflect the citizens’ budget preferences more precisely, thereby enhancing citizen-government communication. However, the efficacies of budget participation remain ambiguous considering both its democratic values and the cost of deliberation. In this study, we test how direct citizen participation by means of participatory budgeting (PB) affects the financial condition of local governments. We use a sophisticated concept of financial condition that encompasses various abilities of local government. We measure the degree of citizen participation as the availability of institutional mechanisms associated with different levels of inclusiveness and authorities determined by South Korean local government ordinances of formal budget participation. Our empirical analysis based on South Korean local governments’ data between 2012 and 2019 reveals that a PB institution with higher participation level further worsens the local financial condition. The adverse effects are mostly identified in the mid-term and long-term financial conditions, whereas the short-term financial condition remains unaffected. The findings imply that direct participation in theory corrects mismatches between bureaucratic and citizen priorities, but, in practice, the citizens may inappropriately direct mid- and long-term oriented public investment and debt management.